A relationship between work environment and employee well-being: a case study at Jabatan Perpaduan Negara dan Integrasi Nasional (JPNIN), Kuching Sarawak/ Angelica Gerit David - David, Angelica Gerit (2016)
The purpose of this study is to examine the relationship between work environment components (workplace bullying, stress, organizational behavior and physical office environment) towards employee well-being at Jabatan Perpaduan Negara dan Integrasi Nasional (JPNIN) in Kuching Sarawak. At the beginning of this study, the purpose, research questions, significant of this study and other relevant for this study is indicated. In other to collect the data, the researcher used questionnaires as an instrument to find out the information from the respondents. The questionnaires consist of three sections including the demographic information, independent variable and dependent variables. All the data that obtained from the questionnaires has been tabulated using the statistical packages for social science software (SPSS) version 21 for data cleaning. The result indicates that independent variables (workplace bullying, stress, organization behavior and physical office environment) have a positive relationship to dependent variable (employee well-being). It shows that all the variables a significant for this research studies.